Solution:
Given: EF//GH, EI//FG and FJ//GI
To prove:
 ΔEFJ ≅ ΔHGI
 Area of parallelogram EFGH = Area of parallelogram FGIJ
Proof:
SN  Statements  Reasons 
1. 
In ΔEFJ and ΔHGI


2.  ∴ ΔEFJ ≅ ΔHGI  By A.A.S statement. 
3.  Area of ΔEFJ = area of ΔHGI  Areas of congruent triangles, from statement 2 
4.  Area of Trapezium EFGI  ΔHGI = Area of Trapezium EFGI  area of ΔEFJ  Subtracting equal triangles from Trapezium EFGI. 
5.  ∴ Area of parallelogram EFGH = Area of parallelogram FGIJ  From statement (4), by whole part axiom. 
Hence proved.